The mobile sleep medicine model in neurologic practice: Rationale and application - Boulos, Mark I.; Chi, Luqi; Chernyshev, Oleg Y. (Frontiers in Neurology, 2022)
Background: Undiagnosed obstructive sleep apnea (OSA) is prevalent in neurological practice, and is a significant contributor to morbidity and mortality. OSA is prevalent in US adults and causes poor quality sleep, as well as significant neurocognitive, cardiovascular, and cerebrovascular impairments. Timely treatment of OSA reduces cardio-cerebro-vascular risks and improves quality of life, however, most of the US population has limited systematic access to sleep medicine care despite its clinical significance. Focus: We discuss the importance of systematic screening, testing, and best practice management of OSA and hypoventilation/hypoxemia syndromes (HHS) in patients with stroke, neurocognitive impairment, and neuromuscular conditions. The goals of this review are to introduce and describe a novel integrated Mobile Sleep Medicine (iMSM) care model, as well as provide the rationale for use of an iMSM in general neurological practice to assist with systematic screening, testing, and best practice management of OSA and HHS. Key points: The iMSM is an innovative, patient-centered, clinical-outcome-based program, which uses a Mobile Sleep Medicine Unit — a “sleep lab on wheels”— designed to improve access to OSA sleep care at all levels of care, from hospital to home. The protocol for the iMSM care model includes 3 levels of operations to provide effective and efficient OSA screening, timely testing/treatment plans, and coordination of further sleep medicine care follow-up. The iMSM care model prioritizes effective, efficient, and patient-centered sleep medicine care; therefore, all parties and segments of care that receive and provide clinical sleep medicine services may benefit from adoption of this innovative approach.